ANALISIS PERATURAN PAJAK UNTUK EKONOMI DIGITAL DAN TRANSAKSI E-COMMERCE - Caroline, Caroline; Loso Judijanto (Prosiding Seminar Nasional Indonesia, 2025)
The rapid growth of the digital economy and e-commerce transactions has presented significant challenges for traditional taxation systems. The high level of cross-border activity and the lack of physical presence of digital businesses make it difficult to determine tax jurisdiction and apply appropriate tax rules. This study discusses the urgency of updating tax regulations in response to the complexities of the digital economy, including the concept of ‘digital nexus’ and various approaches such as digital service tax (DST). Additionally, the importance of international coordination and strengthening national infrastructure is highlighted as efforts to avoid double taxation while creating a fair and effective tax governance framework. With a holistic policy strategy, these challenges can be transformed into opportunities to support sustainable growth in technology-driven economies.